Practical considerations for adaptive strategies by US grazing land managers with a changing climate. Issue 1 (16th March 2023) - Derner, Justin D.; Wilmer, Hailey; Stackhouse‐Lawson, Kim; Place, Sara; Boggess, Mark
Abstract: We outline practical considerations for grazing land adaptations with a changing climate, with an emphasis on the ranch operation scale and specific attention to directional climate changes and increased climate variability. These adaptive strategies fall into two themes: flexibility and learning under uncertainty. Ranches and livestock operations with greater land, social, or other capital resources may have more flexibility. Risk can be reduced for managers (ranchers, farmers, operators, and livestock managers) through participation in conservation or farm policy programs and/or market‐based approaches. Bolstering adaptive capacity across landscapes and time can originate from social capital of operators and strategic collaborations among managers and scientists. As climate diverges from historical baselines and the realm of managers' experiential knowledge, new conceptual frameworks are needed to structure conversations, influence research relevancy and impact, and drive imaginative solutions among researchers, managers, and local communities for socio‐ecological systems. We provide simplified frameworks to help guide conversation, future research, and new imaginative solutions for systems‐scale knowledge needs and adaptation to address increasingly uncertain and complex change at multiple scales. Practical considerations for adaptive strategies by grazing land managers with a changing climate will be accelerated through (1) collaborative efforts among managers and explicitly with science–management partnerships becoming more mainstream, (2) co‐produced research with managers and researchers at ranch scales, (3) development of communities of practice and associated learning opportunities, and (4) continued co‐development and advancement of technologies and tools that result in high uptake adoption by ranch managers. Core Ideas: Directional climate changes and increased climate variability influence practical considerations for adaptation. Overall themes of grazing lands adaptive tools for managers are flexibility and learning under uncertainty. Climate and ecological dynamics are diverging from baselines and the realm of manager's experiential knowledge. Systems‐scale knowledge needs and adaptation address increasingly uncertain and complex change at multiple scales. Collaborative or "co‐produced" research develops new ways to improve applicability of real‐world context.